The metabolic fate of dietary nicotine in the cabbage looper, Trichoplusia ni (Hübner). (August 2018) - Saremba, Brett M.; Murch, Susan J.; Tymm, Fiona J.M.; Rheault, Mark R.
Graphical abstract: Highlights: Oxidative metabolism contributes to nicotine detoxification in Trichoplusia ni . Trichoplusia ni larvae excrete nicotine and its common metabolites. 5′C-oxidation of nicotine was quantitatively the most significant catabolic pathway. The primary metabolite of nicotine detoxification in Trichoplusia ni detected was cotinine. Abstract: Cabbage looper ( Trichoplusia ni ) larvae are generalist herbivores that feed on numerous cultivated plants and weeds including crucifers, other vegetables, flowers, and field crops. Consuming plant material from a wide range of plant species exposes these larvae to a considerable variety of plant secondary metabolites involved in chemical defense against herbivory. The ability of the cabbage looper larvae to detoxify plant secondary metabolites, such as nicotine, has been attributed to the rapid induction of excretion via the Malpighian tubules. However, the role of metabolism in the detoxification of plant secondary metabolites in cabbage looper larvae is not well studied. We investigated nicotine metabolism in 4th larval instar cabbage looper using UPLC-MS/MS analysis to resolve the time course of nicotine metabolism, the kinetic distribution of nicotine, and the presence or absence of major metabolites of nicotine in larval tissue and excretions. The major metabolite found in our analysis was cotinine, with trace amounts of cotinine N-oxide and nicotine N-oxide. The nicotine metabolites detected are similar to those of the nicotine-tolerant Lepidopteran tobacco hornworm ( Manduca sexta ). The results of our study demonstrate that the 5′C-oxidation of nicotine to cotinine is the primary pathway for nicotine metabolism in cabbage looper larvae. This study showed that metabolism of nicotine and subsequent excretion of nicotine and its metabolites occurs in the larvae of the cabbage looper. Our results suggest that 5′C-oxidation in lepidopteran insects is a conserved metabolic pathway for the detoxification of plant secondary metabolites.